PENGARUH PENGALAMAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. KARYA SUKSES SEJAHTERA SURABAYA - Marselinus Dery Hartono; C. Sri Hartati (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2024)
This study aims to determine the effect of work experience, work discipline on employee performance, a population of 40 employees. This study uses a quantitative approach, the data obtained through a questionnaire that has been filled out by several respondents. The method used is multiple linear analysis method.Data analysis was carried out using statistics with SPSS tools. Based on data analysis using the t test, work experience does not have a significant effect on employee performance. Work discipline has a significant effect on employee performance. Meanwhile, based on the results of data analysis using the F test, it is known that simultaneously the variables of work experience, work discipline have a significant effect on employee performance at PT. Success Prosperous Works Surabaya.